Of essential workers and working from home: Journalistic discourses and the precarities of a pandemic economy. (December 2022) - Creech, Brian; Maddox, Jessica
This article considers how reporting about work during the COVID-19 pandemic operated as a field of discourse that challenged the ideological workings of neoliberalism. By documenting the risks and stresses workers of all classes faced during the first year of the pandemic, the reporting began to question neoliberal capitalism as socially unsustainable. Drawing on a corpus of 151 long-form articles and commentary, we show how journalistic discourse structured relationships between different classes of workers and implicated institutions for failing to properly mitigate the risks associated with COVID-19, even though the discourse largely centered on professionals working from home. As the reporting substantiated the precarities revealed by the pandemic as social facts, it challenged presumptions that undergird neoliberal ideologies, though it remains to be seen whether journalism will discursively re-center neoliberal logics in the wake of the pandemic.